15.0k views
0 votes
Complete the square to transform the quadratic equation into the form

(x – p)^2 = q. x^2 - 8x - 10 = 18
A) (x - 8)^2 = 14
B) (x - 4)^2 = 44
C) (x - 8)^2 = -14
D) (x - 4)2 = -44

1 Answer

6 votes

The square of a binomial is written like


(x\pm a)^2 = x^2\pm 2ax + a^2

In your case, you have
2ax=-8x, which implies
a=-4

So, we want to write


(x-4)^2 = x^2-8x+16

But our left hand side is


x^2-8x-10

If we add 26 to both sides, we have


x^2 - 8x - 10 +26 = 18+26 \iff x^2-8x+16=44 \iff (x-4)^2=44

User Dhardy
by
6.2k points